Ashes and sparks : essays on law and justice - Sedley, Stephen (Cambridge ; New York : Cambridge University Press, 2011)
"As a practising barrister, the Rt. Hon. Lord Justice Sedley wrote widely on legal and non-legal matters, and continued to do so after becoming a judge in 1992. This anthology contains classic articles, previously unpublished essays and lecture transcripts. To each, he has added reflections on what has transpired since or an explanation of the British legal and political context that originally prompted it. Covering the history, engineering and architecture of the justice system, their common theme relates to the author's experiences as a barrister and judge, most notably in relation to the constitutional changes which have emerged in the last twenty years in the United Kingdom"--
Includes bibliographical references and index.
Keywords: Law -- Great Britain; Human rights